Ultrasound Anatomy of the Radial Nerve in the Distal Upper Arm. Issue 3 (1st May 2007) - Foxall, Gillian L.; Skinner, Dean; Hardman, Jonathan G.; Bedforth, Nigel M.
Abstract : Background and Objectives: We aimed to describe the ultrasound appearance of the radial nerve in the lateral aspect of the distal upper arm. This procedure was done to identify potential novel sites for ultrasound-guided radial-nerve block. Methods: We scanned the lateral aspect of the distal upper arm in both arms of 50 healthy adult volunteers (equal gender distribution), using a 38 mm, 5 to 10 MHz, linear ultrasound probe (SonoSite MicroMaxx, Hitchen, UK). Three points were defined: A, midway between the anterior process of the acromion and lateral epicondyle of the humerus; B, one third of the distance between A and the lateral epicondyle; C, two thirds of the distance between A and the lateral epicondyle. Subjects' arms were scanned between A and C. We measured the maximal transverse (parallel to skin) and anteroposterior (perpendicular to skin) diameters of the radial nerve and calculated its cross-sectional area. Depth of the radial nerve from the skin surface was measured, and its shape and appearance were noted. Results: At point B, the radial nerve lay in the spiral groove of the humerus, closely associated with the profunda brachii artery and vein. At point C, the nerve had passed through the lateral intermuscular septum and lay between brachioradialis and brachialis muscles. In 99% of arms, the radial nerve was not visible at point A, but became visible between points A and B in 93% of arms. The depth at point B was significantly less than at point C (mean ± SD: 1.21 ± 0.35 vs. 1.71 ± 0.35 cm; P < .001). The measured depth of the nerve was positively correlated ( P < .001) with body mass index and with arm circumference, but not with gender. The radial nerve was oval-shaped at both sites, with a cross-sectional area of 3.1 ± 0.7 mm 2 at point B and 2.9 ± 0.7 mm 2 at point C. Conclusions: Points B and C may represent convenient, novel sites for ultrasound-guided radial-nerve block. The nerve is clearly visualized and has not yet divided into superficial and deep branches. Point C may be the optimal site for radial-nerve block because of the smaller risk of vessel puncture. Our observations also demonstrate the ability of ultrasound to identify nerves at sites not clearly defined by surface anatomic landmarks.